Burnout amongst members of the French-speaking Society of Pediatric and Adolescent Urology (SFUPA). Are there specific risk factors?. Issue 4 (August 2020) - Harper, L.; Alshammari, D.; Ferdynus, C.; Kalfa, N.
Summary: Background: Burnout, which includes emotional fatigue, cynicism and low personal accomplishment is linked to poor job satisfaction, decreased empathy, job withdrawal, increased absenteeism and increased medical errors, and is present among pediatric urologists. Objective: We aimed to determine the incidence of burnout among the members of the French-speaking Society of Pediatric and Adolescent Urology (SFUPA) and determine which external factors, such as marital or familial status, gender, age, type of practice or religious belief, impacted burnout rates. Material and method: We sent all members of the French-speaking Society for Pediatric and Adolescent Urology (SFUPA) an anonymous online questionnaire containing the validated French version of the 22-item Maslach Burnout Inventory – Human Services Survey (MBIHSS). The questionnaire comprised further questions on age, gender, marital status, presence of children at home, type of practice, professional status (trainee, consultant, or academic position), spirituality and whether responders believed they presented signs of burnout. Results: 70 out of 94 members of the SFUPA answered the questionnaire (response rate 74%). The number of responders who presented high scores in one, two or the three domains of the questionnaire were respectively 48.6% (IC 95%: 36–61%), 21.4% (IC 95%: 12.5–33%) and 8.6% (IC 95%: 3–18%). 34.6% of responders who believed they presented no signs of burnout actually did have a high burnout score in at least one domain. There was no significant association between age, gender, having children or being a trainee and the presence of burnout. However, marital status and workplace were significantly associated with presence of signs of burnout. Discussion: Burnout is a distinct type of work-related stress - a state of physical or emotional exhaustion that also involves a sense of reduced accomplishment and loss of personal identity. In our study the most significant factor was working in Academic hospitals which can be associated with administrative workload, long hours and a lack of institutional resources. Being in a couple was also associated with less burnout, thus showing the importance of healthy relationships and sharing on burnout rate. Age, however was not associated significantly with burnout nor was gender, which is in coherence with previous findings. Conclusion: Amongst members of the French-speaking Society of Pediatric and Adolescent Urology, nearly half presented signs of burnout, especially those working in academic hospitals. Marital status also influenced burnout rates. Scientific societies should work on developing tools to identify and accompany affected individuals. Summary Table Main results Table Questionnaire Items Results Number responders/total number of questionnaires 70/94 (74%) Responders presenting a high burnout score in at least one domain 34/70 (49%) Responders presenting a high burnout score in all three domains 6/70 (9% Proportion of "high burnout" responders being single 3/6 (50%) Proportion of "high burnout" responders working in Academic hospitals 6/6 (100%)